Counting efficiency in gamma-ray spectrometry with different sample volumes for the same geometry (Brazilian Journal of Radiation Sciences, 2022)
The aim of this study is to determine an easy and fast method to calculate efficiencies in different volumes, in the same counting geometry, for gamma-ray spectrometry technique. Reference Material Soil IAEA 326 was packed in a 100 mL capacity polyethylene bottle with different masses and volumes, and sealed for about four weeks, prior measurement, in order to ensure that radioactive equilibrium had been reached between 226Ra and its progeny. After this time, they were measured by gamma-ray spectrometry with a hyper-pure germanium detector. The masses of the reference material used were 25, 60, 80, 95 and 128g. The energies of gamma-rays used in this paper are recommended due to the considerations: gamma intensity value, peak quality, spectral region without interference and the gamma- ray energies of the 238U and 232Th series very important for determining the natural radioactivity. The efficiency values obtained compared to the adjusted efficiency values were similar and presented a good correlation coefficient. The performance was acceptable for all different masses studied, indicating results consistent for the method. The proposed method could be useful as a tool for laboratories, dealing with of samples on a routine basis, by reducing the cost on the purchase of another counting geometry and optimizing the use of the detection system, thus improving their performance.
Keywords: gamma-ray spectrometry; counting efficiency; environmental samples